Neurosteroids as endogenous regulators of seizure susceptibility and use in the treatment of epilepsy - Reddy, Doodipala S. (2010)
Neurosteroids such as allopregnanolone are positive allosteric modulators of GABA(A) receptors with powerful antiseizure activity in diverse animal models. Neurosteroids may be endogenous regulators of seizure susceptibility, for example, in catamenial epilepsy. Clinical trials with the synthetic neurosteroid analog ganaxolone in the treatment of refractory partial seizures and infantile spasms have been encouraging. Neurosteroids and analogs such as ganaxolone show promise in the treatment of diverse forms of epilepsy. For an expanded treatment of this topic see Jasper’s basic mechanisms of the epilepsies, 4th ed. (Noebels JL, Avoli M, Rogawski MA, Olsen RW, Delgado-Escueta AV, eds) published by Oxford University Press (available on the National Library of Medicine Bookshelf [NCBI] at www.ncbi.nlm.nih.gov/books).